2018
DOI: 10.15537/smj.2018.12.23136
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude toward hemoglobinopathies premarital screening program among unmarried population in western Saudi Arabia

Abstract: Objectives:To assess the knowledge and attitude toward hemoglobinopathies premarital screening (PMS) program among unmarried population in Jeddah, Kingdom of Saudi Arabia.Methods:A cross-sectional study was conducted among 1039 unmarried males and females from the general population who fulfilled the eligibility criteria. Data was collected from July-December 2017, using an electronic questionnaire to assess the socio-demographic data, knowledge and attitudes of the participants regarding PMS.Results:Approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…And more than 60% of all the participants were in favor of preventing at-risk marriages. 17 Moreover, these participants who were 18-30 years old aware that genetic diseases can be passed from parents to children which support our previous claim. On the other hand, it could be said that the older participants have better knowledge of the impact of genetic diseases on the economy as a result, they support preventing marriage if the couple is found to have a genetic disease since it could be transferred to their children.…”
Section: Discussionsupporting
confidence: 78%
“…And more than 60% of all the participants were in favor of preventing at-risk marriages. 17 Moreover, these participants who were 18-30 years old aware that genetic diseases can be passed from parents to children which support our previous claim. On the other hand, it could be said that the older participants have better knowledge of the impact of genetic diseases on the economy as a result, they support preventing marriage if the couple is found to have a genetic disease since it could be transferred to their children.…”
Section: Discussionsupporting
confidence: 78%
“…Higher family income was also a significant predictor, in agreement with findings from a recent study of the general population in western Saudi Arabia. 13 We also detected an association between the level of PMSGC knowledge and marital status, with previously married participants having a higher knowledge score than those not married before. This is likely to be because these individuals had already attended premarital screening for married couples.…”
Section: Discussionmentioning
confidence: 52%
“…The sample size was calculated using Epi Info STATCALC version 7.2.2.6, with assumptions based on Binshihon et al, who found that 48.9% of the unmarried population in western Saudi Arabia had fair to good knowledge about the premarital screening program. 13 With a 95% confidence level (CI), 5.5% margin of error, 43% expected fair to satisfactory level of knowledge, and a design effect of 20 to permit analysis between the 20 regions, the sample size was calculated as 6220. Finally, 6250 people were targeted and 6500 were approached in case of sample attrition.…”
Section: Methodsmentioning
confidence: 99%
“…17 Concerning positive attitude, one research revealed that Malaysian medical students have positive knowledge and attitude toward breast cancer. 18 Meanwhile, the practice level of the community is moderate, showing that good attitude does not necessarily mean good practice.…”
Section: Discussionmentioning
confidence: 99%